Proceedings of the 19th ACM International Conference on Information and Knowledge Management 2010
DOI: 10.1145/1871437.1871506
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting click-through behavior in aggregated search interfaces

Abstract: An aggregated search interface is designed to integrate search results from different sources (web, image, video, blog, etc) into a single result page. This paper presents two user studies investigating factors affecting users click-through behavior on aggregated search interfaces. We tested two aggregated search interfaces: one where results from the different sources are blended into a single list (called blended ), and another, where results from each source are presented in a separate panel (called non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…In later work, Sushmita et al [25] conducted a similar study with an aggregated interface similar to our blended interface and a blocked interface similar to the one used in Sushmita et al [24]. Results showed that users clicked more on verticals that were presented higher in the blended results and on verticals that were more relevant to the task.…”
Section: Related Work 21 Aggregated Searchmentioning
confidence: 73%
See 4 more Smart Citations
“…In later work, Sushmita et al [25] conducted a similar study with an aggregated interface similar to our blended interface and a blocked interface similar to the one used in Sushmita et al [24]. Results showed that users clicked more on verticals that were presented higher in the blended results and on verticals that were more relevant to the task.…”
Section: Related Work 21 Aggregated Searchmentioning
confidence: 73%
“…A few user studies have investigated search and preference behavior with aggregated search interfaces [24,25,28]. Sushmita et al [24] experimented with two aggregated search interfaces: one similar to our non-blended interface, which did not combine content from different sources in the main results, and a second interface that combined content from different sources in a two-dimensional blocked fashion.…”
Section: Related Work 21 Aggregated Searchmentioning
confidence: 99%
See 3 more Smart Citations